Brexit: towards a deep and comprehensive partnership? - Zuleeg, Fabian (Brussels, 2017)
"Following significant movements of the UK position in response to EU demands, despite the current impasse on Northern Ireland agreement on sufficient progress seems close. Ahead of the 14-15 December European Summit, Fabian Zuleeg explores the likely scenarios that could be considered during the second phase of the negotiations.